Prevalence of NCDs among Rural Households of Dhamrai Upazila, Dhaka - Rahman, Md Mahfuzar; Rahman, Md Atiqur; Sajani, Tabassum Tahmin; Kawser, Abu (Anwer Khan Modern Medical College Journal, 2017)
Background: The emerging pandemic of Non-Communicable Diseases (NCDs) creates a new frontier for health professionals globally. Bangladesh has been facing a dual burden of existing communicable and nocommunicable diseases. The aim of this study was to find out the proportion of NCDs among the rural households. Material and Methods: This descriptive cross sectional study was carried out among 552 respondents and 651 family members suffering from NCDs as respondents by purposive sampling technique from 13th to 15th December, 2015 in different villages of Dhamrai Upazila,Dhaka. Data were collected on a pretested questionnaire by face to face interview. Data were analyzed manually and by using computer. Results: The study revealed that majority of the respondents 77% were Muslims by religion and 52% male, 48% female by sex. About 87% respondents were found within the age 15-55 years and mean age was 38.71±1.73 years. Most of them 73% were literate and only 27% were found illiterate. About 60% were involved in Business, service and 16%, 10%, 9% and 5% were Day Labourer, Garments workers, Farmers and Driver respectively. About 59% respondents monthly income were more than TK 9000. About 46% & 33% respondents found to have 3 & 4 number of family members respectively. The proportion of family members of the respondents suffering from NCDs was estimated to 31%. Among the sufferer 48.7% were male and 51.3% were female. About 71% were found within 21-60 years age group. Diabetes, Hypertension, COPD and CHD were found mostly among 33%, 54%, 26% & 11% of the respondents respectively. Regarding duration of suffering from NCDs 18%, 29%, 31% & 24% were suffering for 3-4 years from diabetes, Hypertension, COPD & CHD respectively. Moreover, 21% had other co-morbidities along with NCDs. Peptic Ulcer Disease, pain, Arthritis, Allergy, Ear infections & Disability were found as common co-morbidities among 49%, 47%, 19%, 12%, 11% & 9% of the respondents respectively. Conclusion: Proportion of NCDs among the rural households are alarming and people are also suffering from various co-morbidities along with NCDs. The study findings demand the strategic plan for surveillance and prevention of NCDs in Bangladesh. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 55-59